EFEKTIVITAS LATIHAN ANKLE WEIGHT DAN LADDER DRILL TERHADAP PENINGKATAN FREKUENSI TENDANGAN SABIT PADA ATLET PENCAK SILAT - Purnawati; M. Salabi; Fitry Nachamory Oemar (Journal Sport Science, Health and Tourism of Mandalika (Jontak) e-ISSN 2722-3116, 2025)
The crescent kick is a high-scoring pencak silat technique requiring rapid lower-limb actions; two commonly used training approaches are ankle-weight (AW) and agility ladder drills (LD), yet comparative evidence in adolescents remains limited. This study examined the effects of AW and LD on crescent-kick frequency and compared their effectiveness. Using a 5-week quasi-experimental pretest–posttest design, twenty male adolescent athletes were equally allocated to AW (n=10) and LD (n=10). The primary outcome was the number of correct crescent kicks in 10 seconds on the dominant side. Analyses employed within-group paired t-tests and between-group independent t-tests (α=0.05). Both groups improved significantly (AW: 14.30±1.34 to 22.50±1.96; Δ=+8.20; t=21.09; p<0.001; LD: 14.50±1.27 to 21.70±1.06; Δ=+7.20; t=24.78; p<0.001). Post-test means did not differ significantly (mean difference 0.80; p=0.275), indicating comparable effectiveness. Coaches may select either approach based on equipment availability, coaching preferences, and periodization phase.